Resiliensi Mahasiswa Ditinjau dari Efikasi Diri dan Dukungan Sosial Pada Kegiatan Program Magang MSIB - Az-Zahra, Dzakirahsalwa; Saragih, Sahat; Rini, Rr. Amanda Pasca (Jurnal Ilmiah Psyche, 2024)
The transition of student activities from regular classes to internship activities may make students experience various difficulties. Therefore, a form of tenacity is needed so for students to able to adapt and bounce back when facing difficulties, so that the internship program can run well and be completed on time. This ability is called resilience. Resilience can be increased by students' belief that they are able to overcome difficulties, commonly called as self-efficacy, and accompanied by social support from the people closest to them. The aim of this research is to determine the relationship between self-efficacy and social support and resilience in students participating in the MSIB internship program. This quantitative research chose students who participated in the MSIB internship program in the “Ruang Belajar Aqil” batch 2-5 as the research subjects. The sampling technique uses incidental sampling technique. In this research, there were 258 participants. The measuring instruments used were The Resilience Scale Wagnild and Young (1987), the Self-Efficacy Scale, and The Multidimensional Scale of Perceived Social Support (MSPSS) compiled by Zimet et al (1998). The data analysis technique in this research uses multiple linear analysis techniques with the help of the IBM SPSS Statistics version 23 program. Based on the correlation test, a score of R = 0.653 was obtained with a significance of p = 0.000 (p < 0.01), meaning that there was a significant positive relationship between self-efficacy, social support and resilience in students who participated in the MSIB internship program.